Perovskite/Silicon Tandem Solar Cells: Marriage of Convenience or True Love Story? – An Overview. Issue 1 (11th September 2017) - Werner, Jérémie; Niesen, Bjoern; Ballif, Christophe
Abstract: Perovskite/silicon tandem solar cells have reached efficiencies above 25% in just about three years of development, mostly driven by the rapid progress made in the perovskite solar cell research field. This review aims to give an overview of the achievements made in this timeframe toward the goal of developing high‐efficiency perovskite/silicon tandem cells with sufficiently large area and long lifetime to be commercially interesting. The developments that led to the recent progress in tandem cell efficiency, as well as the factors currently still limiting their performance, including parasitic absorption, reflection losses, and the nonideal perovskite absorber layer bandgap, are discussed. Based on this discussion, guidelines for future developments are given. In addition, crucial aspects to enable the commercialization of perovskite/silicon tandem solar cells are reviewed, such as device stability and upscaling. Finally, economic considerations show how the number of steps and/or the costs associated to these steps for realizing the perovskite cell must be kept to a minimum to keep up with progress in the field of silicon photovoltaics. Abstract : Perovskite/silicon tandem solar cells have the potential for efficiencies above 30%, at low manufacturing costs. This review article summarizes the development of this emerging technology during recent years, highlighting the progress made on tandem cell performance and analyzing crucial aspects for future developments towards commercialization, such as stability, up‐scaling, toxicity, and production costs.